The Effectiveness of Corner Online Learning During a Pandemic - Sardiman, Sardiman; Purwanto, Didik (Journal Coaching Education Sports, 2022)
This study aims to describe the effectiveness of online learning during the COVID-19 pandemic in PJOK subjects. This study uses a quantitative descriptive research design with a one-shot case study approach using survey methods. Data analysis techniques using quantitative descriptive analysis with percentage data. The results showed that during the COVID-19 pandemic 100% of teachers continued to provide PJOK learning, 66.7% of teachers used online learning methods 22.2% of PJOK learning was by the lesson plan, and 66.7% according to the lesson plans but not coherently 66.7% used WhatsApp group learning media, 66.7 % of students enthusiastic and participating well in learning 77.8% of teachers working with parents of students so that the PJOK learning process continues 44.4% of teachers say learning is by lesson plans 77.8% assessment based on a collection of assignments and exams 88.9% of teachers say assessment on online learning is not effective and 88.9% of obstacles in PJOK learning are difficulty accessing the internet.